High-voltage test and measuring techniques - Hauschild, Wolfgang (Springer Berlin Heidelberg, 2014)
It is the intent of this book to combine high-voltage (HV) engineering with HV testing technique and HV measuring technique. Based on long-term experience gained by the authors as lecturer and researcher as well as member in international organizations, such as IEC and CIGRE, the book will reflect the state of the art as well as the future trends in testing and diagnostics of HV equipment to ensure a reliable generation, transmission and distribution of electrical energy. The book is intended not only for experts but also for students in electrical engineering and high-voltage engineering.